Registro Notable del Puercoespín Arborícola Sphiggurus mexicanus (Rodentia: Erethizontidae) en la Sierra Madre Oriental, México - Lira-Torres, Iván; Sanchez-Rojas, Gerardo; Ojeda-Ramírez, Deyanira; Gómez de Anda, Fabián R. (THERYA, 2014)
Introduction: The Mexican hairy porcupine Sphiggurus mexicanus (Rodentia: Erethizontidae) has been poorly studied in Mexico and is considered threatened according to NOM- 059- ECOL- 2010 (Mexican list of endangered species). Habitat loss due to fragmentation is a major problem for this species throughout its geographic range. Methodology: An adult female Mexican hairy porcupine (Sphiggurus mexicanus) in good health was donated to the Nicolás Bravo Zoo in Tulancingo City, state of Hidalgo, Mexico, in June 2013. Prior to admission to the zoo, the specimen was quarantined in the veterinary school of the Universidad Autonoma del Estado de Hidalgo (UAEH). Results: The porcupine was successfully fed a diet based on alfalfa, mango, mamey (Pouteria sapota), avocado and squash. We found two species of ectoparasites on the porcupine, Amblyomma longirostre and Trichodectes sp. The specimen of Sphiggurus mexicanus was collected at 20.29077Âº N, -98.11047Âº W, near the Pahuatlan River, on the border between the states of Puebla and Hidalgo, in the Eastern Sierra of Mexico. Discussion: This location record is new and is important in that it confirms and documents the presence of the Mexican hairy porcupine Sphiggurus mexicanus, with geographical coordinates, in the Eastern Sierra of Mexico. Habitat connection to the previously known locality 70 km away in the area of Tuzamapan de Galeana, Puebla is not clear. Key words: Eastern Sierra of Mexico, Mexican hairy porcupine, Sphiggurus mexicanus, records